Characterization of a pull-In based μg resolution accelerometer - Dias, R. A. (2010)
The pull-in time of electrostatically actuated parallel-plate microstructures enables the realization of a high-sensitivity accelerometer that uses time measurement as the transduction mechanism. The key feature is the existence of a metastable region that dominates pull-in behavior, thus making pull-in time very sensitive to external accelerations. Parallel-plate MEMS structures have been designed and fabricated using a SOI micromachining process (SOIMUMPS) for the implementation of the accelerometer. This paper presents the experimental characterization of the microdevices that validates the concept and the analytical models used. The accelerometer has a measured resolution of 0.25 μs/μg and an estimated mechanical-thermal noise of 2.8 μg/VHz. Since the bandwidth of the sensor is directly related to the pull-in time (BW = 2/tpi = 180 Hz), the total measured noise floor of 400 μg (110 μs) suggests that the main noise source comes from the building vibrations.